Nationwide overview of the distribution of hepatitis B virus genotypes in Brazil: A 1000-sample multicentre study - Lampe, Elisabeth; Mello, Francisco C. A.; do Espírito-Santo, Marcia P.; Oliveira, Cintia M. C.; Bertolini, Dennis A.; Gonçales, Neiva S. L.; Moreira, Regina C.; Fernandes, Carlos A. S.; Nascimento, Haydée C. L.; Grotto, Rejane M. T. [UNESP]; Pardini, Maria Inês M. C. [UNESP]; de Almeida, Ricardo Wagner; et al. (Microbiology Society, 2017)
The influence of hepatitis B virus (HBV) genotypes in the natural history of the disease and its response to antiviral treatment have been addressed in many studies. In Brazil, studies on HBV genotype circulation have been restricted to specific population groups and states. Here, we have conducted a nationwide multicentre study with an unprecedented sample size representing all Brazilian regions in an effort to better understand the viral variants of HBV circulating among chronic carriers. Seven HBV genotypes were found circulating in Brazil. Overall, HBV/A was the most prevalent, identified in 589 (58.7 %) samples, followed by HBV/D (23.4 %) and HBV/F (11.3 %). Genotypes E, G, C and B were found in a minor proportion. The distribution of the genotypes differed markedly from the north to the south of the country. While HBV/A was the most prevalent in the North (71.6 %) and Northeast (65.0 %) regions, HBV/D was found in 78.9 % of the specimens analysed in the South region. HBV/F was the second most prevalent genotype in the Northeast region (23.5 %). It was detected in low proportions (7 to 10 %) in the North, Central-West and Southeast regions, and in only one sample in the South region. HBV/E was detected in all regions except in the South, while monoinfection with HBV/G was found countrywide, with the exception of Central-West states. Our sampling covered 24 of the 26 Brazilian states and the Federal District and is the first report of genotype distribution in seven states. This nationwide study provides the most complete overview of HBV genotype distribution in Brazil to date and reflects the origin and plurality of the Brazilian population.
Keywords: Brazil; Genotypes; HBV